Overexpression of VEGFα as a biomarker of endothelial dysfunction in aortic tissue of α-GAL-Tg/KO mice and its upregulation in the serum of patients with Fabry’s disease - Lund, N.; Wieboldt, H.; Fischer, L.; Muschol, N.; Braun, F.; Huber, T.; Sorriento, D.; Iaccarino, G.; Müllerleile, K.; Tahir, E.; Adam, G.; Kirchhof, P.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Fabry´s disease is an x-linked lysosomal storage disorder caused by reduced activity of α-galactosidase A (GAL) leading to premature death. Accumulation of the GAL substrate globotriaosylceramide (Gb3) in endothelial and smooth muscle cells is associated with early vascular cell damage, suggesting endothelial dysfunction as a driver of cardio-renal organ failure. Here, the vascular expression of the angiogenic factors VEGFα and its antagonist angiostatin in α-GAL-Tg/KO mice and circulating VEGFα and angiostatin serum levels in Fabry patients and healthy controls were determined. Cryopreserved aortic vessels from 6 α-GAL-Tg/KO and 6 wild type (WT) -mice were obtained and VEGFα-and angiostatin expression was determined by western blotting and visualized by immunohistochemical staining of paraffin aortic rings. VEGFα and angiostatin serum levels were measured by enzyme linked immunosorbent assay in 48 patients with genetically verified Fabry´s disease (50% male) and 22 healthy controls and correlated with disease severity markers (lysoGb3, Albuminuria, NTproBNP, hsTNT, myocardial wall thickness). VEGFα protein expression was significantly increased (1.66 + 0.35 vs. 0.62 + 0.16, *p=0.0009) and Angiostatin decreased (0.024 + 0.007 vs. 0.053 + 0.02, *p=0.038) in aortic lysates from α-GAL-Tg/KO compared to WT-mice. Immunohistochemical staining revealed an adventitial VEGFα signal in α-GAL-Tg/KO mice, whereas no VEGFα signal could be detected in WT-mice aortas. No differences in aortic angiostatin expression could be visualised. Serum level of VEGFα were significantly up-regulated in Fabry-patients compared to healthy controls (708.5 + 426.3 vs. 458.5 + 181.5 pg/ml, *p=0.048) and positively associated with Albuminuria (r=0.82, *p<0.0001), elevated NTproBNP (r=0.87, *p<0.0001) and hsTNT values (r=0.41, *p=0.048) in male Fabry patients. For Angiostatin no significant difference could be revealed between Fabry patients and healthy controls (747.6 + 390.3 vs. 858.8 + 599.3 pg/ml). In conclusion, overexpression of VEGFα and downregulation of angiostatin in aortic tissue of α-GAL-Tg/KO mice support the hypothesis of an underlying vasculopathy in Fabry´s disease. Elevated VEGFα serum levels were also observed in Fabry patients and were positively associated with elevated markers of organ manifestation in males. These findings suggest, that angiogenetic markers, such as VEGFα, may be potentially useful biomarkers for the detection of endothelial dysfunction in classical Fabry´s disease.